"'Ninja' levels of focus": Therapeutic holding environments and the affective atmospheres of telepsychology during the COVID-19 pandemic. (August 2021) - Downing, Leanne; Marriott, Heather; Lupton, Deborah
Abstract: The COVID-19 crisis in Australia led to a rapid increase in the use of telehealth services to offer psychological therapy (often referred to as 'telepsychology'). In this article, we discuss the intersection of the social psychology concepts of therapeutic holding spaces and containment with more-than-human theory as it relates to Australia's mental health sector during the COVID-19 crisis. Drawing on our recent qualitative survey research into Australian psychologists' use of telepsychology during the crisis, we consider the ways that they worked to build and maintain therapeutic holding spaces and alliances over teleconferencing platforms during this extraordinary time of social crisis and isolation. We explore and contextualise three important findings from our study: 1) the limited viewing area of a flat screen makes it difficult for therapists to read and respond to their client's body language and requires different forms of returned bodily gestures in order to show empathy; 2) most respondents implemented different affective and relational strategies online to ensure they were not missing important non-verbal cues from their clients; and 3) the traditionally 'safe' therapeutic holding space created in face-to-face therapy can be easily subverted by client-end interruptions, and concerns around safety or personal privacy in the client's home environment. In bringing these issues to the fore, we highlight the online therapeutic holding space as a temporally and socially situated human-technological assemblage in which a series of affective, spatial, relational and sense-making agencies coverage, opening or closing off capacities for therapists and their clients. Highlights: Psychology holding spaces as affective atmospheres. Australian psychologists' transition to telehealth technologies during COVID-19 crisis. Qualitative survey of Australian psychologists' experiences of telehealth during pandemic. Psychologists use different affective and relational strategies during telehealth consults. Telepsychology requires clients/patients to create their own 'safe' therapeutic environment.